Shelter Belt Plantations Effectively Check Sand Deposition in Indira Gandhi Canal - Upadhyaya, A. K. (Indian Forester, 1991)
The observations recorded each month for one year on Mohangarh distributory, off taking from 1439 R.D. of the Indira Gandhi Main Canal, revealed that afforestation on critical wind-ward side of the canal effectively reduces sand deposition in canal. It was found that one and two year old plantations reduced sand deposition by 0.513 m3 and 1.023 m3 per running metre length of the canal respectively. The plantations so raiesd saved desilting cost by Rs. 6,156 Rs. 12,276 per kilometre in one year in the case of one and two year old plantations respectively.